Rehabilitation characteristics and patient barriers to and facilitators of ACL reconstruction rehabilitation: A cross-sectional survey. (March 2021) - Walker, Adam; Hing, Wayne; Lorimer, Anna; Rathbone, Evelyne
Abstract: Objectives: To investigate patient-reported rehabilitation characteristics and barriers to and facilitators of ACL reconstruction rehabilitation. Design: Survey-based study. Setting: Online survey platform. Participants: Adults 1–20 years post ACL reconstruction (n = 304). Main outcome measures: 1) rehabilitation characteristics, 2) barriers to and facilitators of rehabilitation. Results: Fear of re-injury (43.8%) was the highest rating barrier to rehabilitation adherence, while a good relationship with your rehabilitation provider was regarded as the most important factor (83.6%) in facilitating rehabilitation. Rehabilitation frequency reduced across the duration of rehabilitation from most commonly 1 x week (38.2%) in the first three months to once every month (26%) from 6 to 9 months. Almost all participants (95.7%) consulted a rehabilitation provider for the first six months. Only 43.4% of respondents returned to their previous level of sport. The exploratory analysis identified that low barriers to rehabilitation and a longer duration of supervised rehabilitation are associated with a faster return to sport, greater likelihood of return to previous level of sport and fewer reported ongoing problems with the knee. Conclusions: This cross-sectional survey provides insight into the patient's experience of rehabilitation practices and a patient's perspective on the key barriers to and facilitators of ACL rehabilitation adherence and participation. Highlights: Fear of re-injury is a major barrier to rehabilitation adherence. The therapeutic relationship was rated as most important in completing rehabilitation. A longer duration of supervised rehabilitation is associated with improved outcomes. Low barriers to rehabilitation is associated with improved outcomes.